Associating Parental Efficacy with the Utility of Smart Devices: A Cross-Sectional Study of Their Role in Alleviating Maternal Parenting Concerns among Infants Aged 6-11 Months - Ryuta Onishi; Hanami Tone; Minori Kubota; Nana Chino; Funa Maruyama (MDPI AG, 2023)
In digital societies, the use of smart devices to solve childcare problems has become commonplace. Mothers are influenced both positively and negatively by smart devices used to resolve childcare concerns. Focusing on parental self-efficacy, this study identified the factors associated with relief and anxiety caused by the use of smart devices to eliminate parenting concerns among mothers with infants. A random sampling cross-sectional survey was administered to 257 Japanese mothers with infants aged 6-11 months. Structural equation modeling was used to explain the relief and anxiety caused by their use of smart devices in terms of maternal demographics, parental self-efficacy, smart-device dependence, and confidence in their ability to discriminate information. Mothers with high parental self-efficacy experienced increased relief and reduced anxiety by using smart devices to address concerns about child-rearing practices. Mothers who were highly dependent on smart devices felt more secure with their use of smart devices. Homemakers and highly educated mothers who used smart devices because of concerns regarding child health and development experienced more anxiety. Parenting professionals need to recognize the effectiveness of smart devices as a tool to relieve anxiety in parenting and provide additional support for parents to improve their parenting self-efficacy.